The Role of the Government's Internal Control System and Human Resource Competence on the Quality of Financial Reports With Leadership Commitment as Moderation - Lubis, Destri Maulina; Khoiru Rusydi, Mohamad; Prastiwi, Arum (Riviera Publishing, 2023)
Quality financial reports can provide information about an organisation's performance, financial position and changes in a reliable, relevant way that can be understood and compared. This study aims to empirically examine the effect of the government's internal control system and human resource competence on the quality of financial reports with leadership commitment as a moderating variable. This research recruited 680 financial managers at the Ministry of Public Works and Public Housing as respondents. Research data were analysed using the SEM-PLS method by using the SmartPLS version 3.2 application as a data processing tool. The findings show that the government's internal control system and human resource capacity significantly affect the quality of financial reporting. A strong and structured internal control system provides a solid foundation for producing reliable and relevant financial reporting by applicable standards. In addition, high human resource capabilities in accounting and internal control can help improve the quality of financial reporting. This research implies providing a deeper understanding of the factors influencing the quality of financial reports within the government context, urging the government to enhance investments in the development of human resource competencies, particularly in terms of a more profound comprehension of accounting and financial reporting. Furthermore, this study could have a significant impact in enhancing the quality of financial reporting within the governmental environment and potentially in other organizations as well.